The role of integrin traffic regulators Rab21 and Swip1 in epithelial-to-mesenchymal transition of mouse breast cancer cells - Pham, Trinh (My University, 2025)
BACKGROUND: Breast cancer is the most common cancer in women worldwide. Although the disease is curable at early stages, it becomes incurable once metastasis occurs. Therefore, there is significant interest in understanding the metastatic process to identify potential treatments for invasive breast cancer. Epithelial-to-mesenchymal transition, or EMT, is a critical event in breast cancer metastasis. During this process, epithelial cells lose their apicalto-basal polarity and adhesion to adjacent cells while increasing their adhesion to the surrounding microenvironment and acquiring invasive abilities. These changes are due to the altered expression and functions of cell-ECM adhesion receptors, integrins, and cell-cell adhesion receptor, E-cadherin. These receptors are constantly shuttled between the plasma membrane and the endosomal compartments through endocytosis and exocytosis. Endocytic trafficking has been shown to play an important role in regulating cancer cell migration, as this process may be altered in response to different EMT signalling pathways and control the availability of several EMT signalling molecules on the plasma membrane. Indeed, integrin endocytosis has been linked to cancer metastasis. Rab21, a key regulator of endosomal integrin traffic, alters cell adhesion and migration of breast cancer cells by controlling integrin endocytosis via the CG pathway. Furthermore, high expression of Swip1 (Swiprosin-1, or EFHD2), an actin- and Rab21-binding protein that functions as an integrin adaptor in the CG endocytosis pathway, correlates with a poor prognosis in triple-negative breast cancer. However, the relevance of Rab21 and Swip1 in controlling cell migration through EMT processes are not fully understood. OBJECTIVES: The aim of my thesis is to further investigate the regulatory effects of Rab21 and Swip1 in breast cancer metastasis, particularly in EMT, with a focus on two aspects: 1) the role of Rab21 and Swip1 in controlling the endocytosis of integrin and E-cadherin, and 2) the effects of Rab21 and Swip1 on cell polarity in EMT. METHODS: Metastatic YEJ cells, derived from lung’s micro-metastatic tumor of breast cancer mouse model, Rab21 KO YEJ cells, and Swip1 KO YEJ cells were used in the study. Endocytosis of integrin β1 and E-cadherin was analyzed using a microscopy-based endocytosis assay. The cell polarity was studied using micropatterning technique, in which the position of the centrosome (polarity marker) was analyzed in a restricted condition of cell doublets seeded on H-shape micropatterns. RESULTS: Swip1 affected the endosomal traffic of both E-cadherin and integrin β1. While Swip1 depletion increased the level of internalized E-cadherin, it reduced the uptake of integrin β1. These results indicate that E-cadherin and integrin β1 are taken up via different endocytosis pathways and that Swip1 might play a role in another endocytic route besides the CG pathway. In addition, upon the depletion of Swip1, mesenchymal cells altered their polarity. The control cells showed a mesenchymal-like polarity with centrosomes of cell doublet facing towards the edges of H patterns, while centrosomes in Swip1 KO cells instead stayed closer to the junction, indicative of a partial transition towards a more epithelial state . CONCLUSION: My study supports that Swip1 is a regulatory protein in EMT and suggests that this regulation is exerted through the control of E-cadherin and integrin β1 endocytosis in breast cancer. More studies are needed to understand the underlying mechanism of endosomal changes in EMT progression. Overall, my findings contribute to the current understanding of Swip1 in EMT, suggesting Swip1 as a potential therapeutic target for breast cancer treatment.
Keywords: EMT, integrin endocytosis, E-cadherin endocytosis, cell polarity, Rab21, Swip1